Beauty and the Cosmetic Secret - Heggenstaller, Alessandra K.; Rau, Asta; Coetzee, Jan K.; Smit, Ria; Ryen, Anne (Qualitative Sociology Review, 2019)
Cosmetic surgery is often linked to the perception that women who resort to cosmetic interventions to alter their physical appearance are vain, superficial, and narcissistic. Few investigations have acknowledged and explored the individual’s personal motivations and experiences of her action and choice with regards to aesthetic surgery. By focusing on subjective experience, alternative insights can be gained on the cosmetic procedure(s) and on how their reshaped body influences an individual’s lifeworld experience. The article explores the perceived benefits and consequences of reshaping, enhancing, and/or reducing a perceived flaw or shortcoming of the body. From this exploration the focus moves to the individual’s subjective and intersubjective perceptions: how she motivates and justifies her physical transformation whilst keeping private, and at times hiding, her surgical intervention. Drawing on narratives from several women, we attempt to understand how they experience cosmetic surgery in terms of their personal sense of self and their everyday social reality.